Preparation of modified release diltiazem HCl capsule by complexation with ion exchange resin - Eman B.H. Al-Khedairy; Alaa A. Abdulrasso; Jenan M. AL-Mosawi (University of Mosul, 2011)
Background: Diltiazem HCl is a calcium channel blocker drug used in the treatment of angina pectoris and hypertension. Objective: To prepare a sustained release diltiazem HCl capsule by complexation with polystyrene sulfonate strong cation exchange resin (dowex®50wx4) as a complexing and retarding agent. Methods: The effect of stirring time and drug: resin ratio on diltiazem HCl loading on dowex®50wx4 was studied. Drug resin complexes were characterized by Fourier Transform Infrared (FT-IR) spectroscopy. The release of drug from the complexes was examined in pH 1.2 and pH 6.8 separately in comparison with pure drug and with commercially available sustained release products Tildia® 120mg capsule and BITildiem ® 120mg tablets Results and conclusion: Most efficient loading was obtained using 1:2 and 1:2.5 drug:resin ratio with stirring time of 60 and 30 minutes respectively. The resultant complexes only retard the release of diltiazem HCl when compared with pure drug while the sustained release product was obtained by coating the complex with carnauba wax and the retardation increased as a function of wax concentration. 20% of wax coated complex gave the release profile approximately similar to the marketed sustained release product of diltiazem HCl, Bi-Tildiem® (Sanofi-France) 120 mg tablets.